Factors Affecting Tourist Visits To Merese Hill In Central Lombok Regency - Faiqotul Mala; Hikmatul Hasanah (Politeknik Internasional Bali, 2025)
Tourism plays a vital role in regional economic development, particularly in priority destinations such as Mandalika in Central Lombok, yet limited research has examined the key determinants of tourist visits to specific sites within this area. This study aims to assess the effects of attractiveness, facilities, accessibility, and promotion on the number of tourist visits to the Merese Hill tourist destination, which is part of the Mandalika Special Economic Zone (KEK), Central Lombok. The research addresses a gap in understanding how these four factors interact to influence visitor behavior in newly developed tourism areas. The study adopts a quantitative approach using a multiple linear regression model. Primary data were collected through accidental sampling by distributing questionnaires to 100 tourists who visited Merese Hill in June 2025. The findings revealed that the four independent variables significantly affect the level of tourist arrivals, both simultaneously and partially. Among them, attractiveness emerged as the most influential factor, followed by promotion, facilities, and accessibility. These findings underscore the importance of managing destination attractiveness and optimizing digital promotion strategies to strengthen Mandalika’s competitiveness in the national and international tourism markets.